Impact of Global Risks on Economic Downturn in Countries Worldwide: Analysis of the Causes of the Situation and Opportunities for Growth Recovery - Kryvoviaziuk, Ihor; Britchenko, Igor; Lipych, Liubov; Kravchuk, Pavlo; Halaziuk, Nataliia; Burban, Oleksandr (Emerald Publishing Limited, 2025)
The purpose of the article is to study the opportunities for resuming the economic growth of economies, considering the impact of global risks on its dynamics. The article provides a comprehensive analysis of the economic growth dynamics of over 200 countries from 1961 to 2023, revealing a general trend of declining growth rates, which is confirmed by the data of observations of GDP dynamics in the USA, Great Britain, Germany, Albania, Ukraine, Mongolia, China, Paraguay, Indonesia, and Sudan. It is defined that these trends are caused by the negative impact of global risks on the dynamics of economic growth of world countries. A contemporary map of the interconnections of categories and types of global risks is presented, illustrating the intertwining of geopolitical, economic, social, environmental, and technological risks. A selection of the five most influential global risks that affected the economic downturn of the world economy from 2006 to 2023 has been formed through logical-structural analysis and generalization method, demonstrating the predominant influence of economic and environmental factors. The analysis of the unique causes of economic downturn under the influence of global risks, conducted using the Ishikawa diagram, allowed to include a set of economic, environmental, social, geopolitical, technological, and other causes. The proposed political-legal, market, organizational-economic, and financial-investment mechanisms for accelerating economic recovery define the priority directions for restoring economic growth, considering the impact of global risks. The provided suggestions have practical significance for the elaboration of economic development strategies for countries to restore economic growth.
Keywords: global risks; economic downturn; GDP; logical-structural analysis; Ishikawa diagram